Giant Amoebic Liver Abscess: A Rare Diagnosis in a Rural Setting of Sub-Saharan Africa - Cyril Jabea Ekabe; Jules Kehbila; Njinju Asaba Clinton (Journal of Parasitology Research)
Background. Extraintestinal amoebiasis is an uncommon complication of Entamoeba histolytica infection, occurring in about 5-10% of patient. Prompt diagnosis and management is essential to prevent complications. However, diagnosis and management in resource-limited settings is very challenging owing to limited diagnostic tools and nonspecific clinical symptoms. Therefore, our case report underscores the role of incisive clinical evaluation, basic investigation, and nonsurgical management of giant amoebic abscess in resource-limited settings. Case Presentation. A 13-year-old female Cameroonian presented with subacute onset of upper abdominal pain, high fever, and chest pain for one week. Before presentation, she had been on treatment at a local traditional practitioner during which her symptoms worsen. After clinical evaluation and basic investigation, she was diagnosed with a giant amoebic liver abscess. She was resuscitated and placed on nonsurgical management. Follow-up after 1 month was significant for complete recovery. Conclusion. Amoebic liver abscess is a rare complication of Entamoeba histolytica infection with devastating complications. The diagnosis of this disease requires high index of suspicion in resource-limited settings. Good clinical evaluation and timely nonsurgical therapy can provide recovery to some patients.